A Rare Occurrence of Primarily Extranodal Spinal Epidural Lymphoma With Spinal Cord Compression and Invasion to the Thoracic Cavity - Seok, Min-Cheol; Madadi, Ahmad Khalid; Mosleh, Mohammad Mohsen; Chang, Sun Hee; Sohn, Moon-Jun (Brain tumor research and treatment, 2023)
A 41-year-old man suffered from progressive radiculomyelopathy caused by spinal epidural mass primarily encasing the spinal cord at the cervicothoracic vertebrae that extended into the thoracic cavity through the neural foramen. An urgent decompressive laminectomy and epidural tumor resection were performed to prevent neurological deterioration and effective spinal cord decompression. The histopathologic diagnosis was diffuse large B-cell lymphoma. As first-line treatment for stage II extranodal lymphoma, he received 6 cycles of R-CHOP (rituximab/cyclophosphamide, hydroxydaunorubicin, Oncovin, and prednisone) chemotherapy. Consequently, follow-up positron-emission tomography CT and MR images demonstrated a complete metabolic response (Deauville score 1). This rare occurrence of primarily extranodal spinal epidural lymphoma with limited disease will be presented in a literature review.